Induction of Hemeoxygenase-1 Reduces Renal Oxidative Stress and Inflammation in Diabetic Spontaneously Hypertensive Rats - Ahmed A. Elmarakby; Jessica Faulkner; Babak Baban; Jennifer C. Sullivan (International Journal of Hypertension, 2012)
The renoprotective mechanisms of hemeoxygenase-1 (HO-1) in diabetic nephropathy remain to be investigated. We hypothesize that HO-1 protects the kidney from diabetic insult via lowering renal oxidative stress and inflammation. We used control and diabetic SHR with or without HO-1 inducer cobalt protoporphyrin (CoPP) treatment for 6 weeks. Urinary albumin excretion levels were significantly elevated in diabetic SHR compared to control and CoPP significantly attenuated albumin excretion. Immuno-histochemical analysis revealed an elevation in TGF-β staining together with increased urinary collagen excretion in diabetic versus control SHR, both of which were reduced with CoPP treatment. Renal oxidative stress markers were greater in diabetic SHR and reduced with CoPP treatment. The increase in renal oxidative stress was associated with an elevation in renal inflammation in diabetic SHR. CoPP treatment also significantly attenuated the markers of renal inflammation in diabetic SHR. In vitro inhibition of HO with stannous mesoporphyrin (SnMP) increased glomerular NADPH oxidase activity and inflammation and blocked the anti-oxidant and anti-inflammatory effects of CoPP. These data suggest that the reduction of renal injury in diabetic SHR upon induction of HO-1 are associated with decreased renal oxidative stress and inflammation, implicating the role of HO-1 induction as a future treatment of diabetic nephropathy.